Depolymerization of Kraft Lignin via tert-butoxide-Assisted Oxidation - Shin Hun Yi; Jo, Seong Mu; Sung-Soo Kim (한국고분자학회 2021년도 추계학술대회 연구논문 초록집 제46권 제2호, 2021)
The valorization of lignin, which is an abundant natural source of aromatic compounds from lignocellulosic biomass, has attracted great attention and widely investigated as an eligible method for the renewable production of value-added chemicals and materials from biosourced feedstocks. Since the reactivity of lignin substantially depends on the structural heterogeneity and the type of functional group, the development of an effective technique converting heterogeneous lignin into well-defined compounds having uniform properties is required to utilize lignin as a sustainable source of bio-derived materials. In this study, we demonstrate tert-butoxide-catalyzed oxidation method to generate oligomeric lignin fragmentation from kraft lignin through the cleavage of the ether bond in lignin structure.